Cooling performance of a pump-driven two phase cooling system for free cooling in data centers. (25th February 2016) - Ma, Yuezheng; Ma, Guoyuan; Zhang, Shuang; Zhou, Feng
Highlights: A magnetic pump is used in the two-phase cooling system. The maximum cooling capacity reaches 3.429 kW and EER is 12.9 at the indoor and outdoor temperature difference of 10 °C. The maximum cooling capacity almost increases linearly with the indoor and outdoor temperature difference. Abstract: The energy consumption of data centers is increasing rapidly with the development of technology. In order to reduce the energy consumption, free cooling technology instead of the conventional refrigeration system is feasible in the cold season. In the present work, a pump-driven two phase cooling system which is an excellent free cooling technology was developed and the prototype was investigated experimentally. The experimental results show that the efficiency of the magnetic pump was 7.7% at the motor frequency of 22 Hz, the cooling capacity of the system was able to reach 3.429 kW and 9.241 kW when the temperature differences between indoor and outdoor were 10 °C and 25 °C, respectively, and the EER were 12.9 and 29.7, which are extremely higher than the conventional refrigeration system.